ICT AS A SUPPORT FOR THE RETENTION OF INFORMATION IN SELF-GUIDED TOURS: THE CASE STUDY OF THE MUSEO DE LAS CULTURAS COTACACHI - Bedón Suárez, Nelson Iván; Benítez Bastidas , Nhora Magdalena; Cevallos Calapi, Raúl Clemente; Bedón Arciniega, Ronnie Alejandro (Tierra Infinita, 2023)
With a diverse collection of historical objects and exhibits, the Cotacachi Cultures Museum is an important cultural institution in Ecuador. The aim of this study was to implement a mobile web prototype application to enhance information retention in self-guided tours within the museum as an added value to the visitor's experience. The use of the cellphone as an educational tool offered new opportunities in learning about cultural heritage. The platform utilized in this study was Storymap, which consisted of an ArcGIS Online website linked through QR codes, providing detailed multimedia and textual information about the collection of historical objects and exhibits. This demonstrates that the use of Information and Communication Technology (ICT) in museums has many advantages, and its applications evolve with technological advancements. In this study, it facilitated self-guided interpretation of the museum's cultural heritage. The results of this article were evaluated at two points in time: the first without the use of the mobile web prototype application and the second with the support of this application. It was observed that there was greater information retention with the use of the technology proposed in this study, making it a positive alternative for learning during self-guided tours.
Keywords: ICT; ArcGIS; QR code; museum, Cotacachi